Three sources of silicon in biomass production of rice (Oryza sativa L.) under controlled conditions - Padilla-Castro, Cesar Franco (2022)
A pot experiment was conducted in the campus of La Molina National Agrarian University in order to evaluate the effect of rice husk ash, ladle furnace slag and potassium silicate on the soil chemical properties and biomass of rice (Oryza sativa L.) cv. ‘Fedearroz 60’, using topsoil from a commercial paddy field at Aucayacu, Huanuco, Peru. Doses were calculated taking into consideration each product available Si (SiA), for reaching concentrations of 100, 200 and 400 ppm (w / w) of SiA in soil before sowing. Control pots without any silicon amendment were considered as well. A completely randomized design with factorial arrangement (3 × 4) was used to assess the Si absorption by plant tissues, final SiA in soils, roots volume, whole plant’s dry weight, tillering capacity, panicles per plant and average spikelets per panicle. Salinity and pH of the growing media were registered weekly. Also were environmental temperature, and light intensity on a daily basis. Results showed that potassium silicate 200 ppm sustainably increased SiA in soils and Si in plant tissue, however the yield components were not positively influenced. Ladle furnace slag increased SiA in soils too, nonetheless for doses of 200 ppm and 400 ppm, symptoms of severe nutritional problems appeared. Rice husk ash did not show statistical significance on SiA in soils, Si in plant tissue, nor yield components. It was concluded that for such soil and weather conditions involved in this experiment, silicon increases in soil and tissues had no influence on rice yield components. In spite of this, ladle furnace slag exhibited an outstanding liming capacity and rice husk ash, a great amount of P, K and micronutrients.